PENGEMBANGAN INOVASI PEMBERDAYAAN IKM BARANG JADI KARET - Dewi Auditiya Marizka; Yandra Arkeman; M. Syamsul Maarif (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2014)
After the economic crisis in 1997, the growth of Big and Medium Scale Industries (MBI)have been slowing down. The perspective of business returns to SME’s. Meanwhile, the problemsof rubber SME’s products, some of them, have been known as slow technology innovation, slowoutput growth (productivity) and lack of working capital. To maintain the competition in themarket, rubber SME’s products must accompany some strategies, in order to survive in themarket and having a bargaining position. This paper just made a recommendation of a model tooptimize the growth of rubber SME’s products. The spread and diffusion of MBI as a leader torubber SME’s products as follower can be done by making some assumptions which must be doneby both parties. By doing this, rubber SME’sproducts could enhance their function in the economyand thus, They will have a secure market to support the economy and sustainability of economicgrowth. To increase the parameters of productivity can be implemented in some ways. The growthof investment, return of capital, working hours, and the growth of human resources quality can bemaintain as the engine of growth for rubber SME’s products. To perform this, They could dothrough raised of the saving, lower inflation and real costs through government’s policy.Thedevelopment of industry should not be imposed only through MBI. The participation of rubberSME’s products should be in the perspective of the government. As it has been mentioned above,the sustainability growth of rubber SME’sproducts must be integrated with the growth of MBI.The government should realize that most of Indonesia population works in this sector, thereforethe growth of this sector will be the locomotive engine of people’s economy.